Pengujian Modulus Elastisitas Lentur Kayu Tembusu (Fragraea fragrans) di Pekanbaru - Monica MG, Intan; Alfian Kamaldi; Andre Novan; Marlaily Idris (SAINSTEK, 2024)
The flexural modulus of elasticity (MOE) is a critical parameter in assessing the mechanical performance of wood, particularly for structural applications. This study investigates the MOE of Tembusu wood (Fragraea fragrans), a tropical hardwood renowned for its durability and versatility in construction and furniture production. Specimens were prepared following SNI 03-3960-1995 standards, ensuring consistency in dimensions and testing protocols. A three-point bending test was employed to evaluate the flexural MOE under controlled laboratory conditions. The results reveal that Tembusu wood exhibits a high flexural modulus, averaging 10.000 MPa, making it comparable to other hardwood species used in structural applications. Additionally, microscopic analysis of wood fibers indicated a correlation between the density and elastic behavior of the material. The study concludes that Tembusu wood possesses excellent bending properties, demonstrating its suitability for beams, joists, and other load-bearing applications. Recommendations for further research include exploring the effects of environmental factors such as humidity and temperature on the long-term performance of Tembusu wood. This research contributes to the growing body of knowledge on sustainable wood materials for engineering applications.